The identification of genetic pathways involved in vascular adaptations after physical deconditioning versus exercise training in humans. Issue 3 (8th November 2012) - Lammers, Gerwen; van Duijnhoven, Noortje T. L.; Hoenderop, Joost G.; Horstman, Astrid M.; de Haan, Arnold; Janssen, Thomas W. J.; de Graaf, Mark J. J.; Pardoel, Elisabeth M.; Verwiel, Eugène T. P.; Thijssen, Dick H. J.; Hopman, Maria T. E.
<x xml:space="preserve">Abstract</x> Physical inactivity and exercise training result in opposite adaptations of vascular structure. However, the molecular mechanisms behind these adaptations are not completely understood. We used a unique study design to examine both vascular characteristics of the superficial femoral artery (using ultrasound) and gene expression levels (from a muscle biopsy) in human models for physical deconditioning and exercise training. Initially, we compared able‐bodied control subjects (n = 6) with spinal cord‐injured individuals (n = 8) to assess the effects of long‐term deconditioning. Subsequently, able‐bodied control subjects underwent short‐term lower limb deconditioning using 3 weeks of unilateral limb suspension. Spinal cord‐injured individuals were examined before and after 6 weeks of functional electrical stimulation exercise training. Baseline femoral artery diameter and hyperaemic flow were lower after short‐ and long‐term deconditioning and higher after exercise training, whilst intima–media thickness/lumen ratio was increased with short‐ and long‐term deconditioning and decreased with exercise training. Regarding gene expression levels of vasculature‐related genes, we found that groups of genes including the vascular endothelial growth factor pathway, transforming growth factor β1 and extracellular matrix proteins were strongly associated with vascular adaptations in humans. This approach resulted in the identification of important genes that may be involved in vascular adaptations after physical deconditioning and exercise.